Woman weaving a Chilkat blanket, Alaska, ca. 1905 - University of Washington Libraries
In this photograph, a woman works on a Chilkat ceremonial dance blanket using a frame loom. The warp threads, made from cedar bark covered with mountain goat wool, hang in bundles from the top bar. The weaver has completed the border on three sides and is beginning to weave the design in the center. She has carefully placed newspapers over the edges of her blanket to protect the finished portion. A closer look at the image reveals that the newspapers originated in California and are dated January 12, 1904. Traditionally, men created the designs and painted them on boards which the women used as patterns for their weaving. The Chilkat are a coastal Tlingit people. Photographers Lloyd V. Winter and Percy E. Pond opened their Juneau, Alaska, studio in 1893, and documented the people and places of southeastern Alaska until the mid-1940s. (Victoria Wyatt, Images from the Inside Passage: An Alaskan Portrait by Winter & Pond, pp. 13-14.)